Assessing Quality of Education: A Comparative Study between Private and Government Schools of Kathmandu (Samriddhi Journal of Development Studies, 2024)
Quality of education determines the quality of human resources of any country making education a cornerstone of societal and personal development. The two educational systems in Nepal- private and government schools have a disparity and the lack of comparative analysis pointing out the indicators of quality education is missing. Government schools in Kathmandu are facing serious challenges that affect the quality of education they provide. This study aims to understand the quality of education in private and government schools focusing through grade 6 to 10 where teaching methods, infrastructures, academic performances and dropout rates are compared. The research used a cross sectional research design to collect data and the data was collected using a mixed method approach to neutralize the limitations where 2 private and 2 government schools of Kathmandu. The analysis of the data revealed that the gap in providing quality education is as significant as people assume it to be. Private schools comparatively are performing better in academic performances where the average score is 0.23 higher in grade 10 than government schools. It was also found that the teaching methods are better in private schools compared to the government. The teachers also felt that focusing on practical learning, integration of technology while the parents are equally involved in their child’s education brings better results and impacts the quality of education. The findings suggest that government policies should be stronger for government schools and even provide teacher training frequently in this fast paced world.